Pharmacokinetic interactions between three SGLT2 inhibitors and telmisartan: A focus on empagliflozin, ertugliflozin, and henagliflozin - Xin Zhou; Yanru Deng; Caihui Guo; Ying Li; Yuhao Fu; Zhi Wang; Zhanjun Dong (PLoS ONE, 2026)
Background Patients with type 2 diabetes mellitus (T2DM) usually accompany with the occurrence of high blood pressure, necessitating a combination of treatments. This includes sodium-glucose co-transporter 2(SGLT2) inhibitors like empagliflozin, ertugliflozin, and henagliflozin, and antihypertensives like telmisartan. Both classes interact with transporters like P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP), with telmisartan further inhibiting several, including organic anion transporting poly-peptide (OATP) 1B1/1B3. Objective Despite their common use, pharmacokinetic interactions between these drugs remain underexplored. This study aims to investigate the potential pharmacokinetic interaction between three specific SGLT2 inhibitors and telmisartan. Methods Rats were divided into twelve groups, with six rats per group, and received different combinations of empagliflozin, ertugliflozin, henagliflozin, and telmisartan. Drug concentrations were measured using ultra-performance liquid chromatography-tandem mass spectrometry, and mRNA expressions through quantitative reverse transcription polymerase chain reaction (RT-qPCR). Results Our study manifested that telmisartan increased the plasma concentration-time curves (AUC 0-t and AUC 0–∞ ) and the maximum plasma concentrations (C max ) of empagliflozin, whereas the apparent clearance (CL z/F ) and apparent volume of distribution (V z ) significantly decreased(all p ＜ 0.05). Similarly, telmisartan increased the AUC 0-t , AUC 0-∞ and C max of henagliflozin and decreased the CL z/F (all p ＜ 0.05). When coadministered with ertugliflozin or henagliflozin, the AUC 0-t and AUC 0–∞ of telmisartan decreased significantly and the CL z/F increased significantly(all p ＜ 0.05). Furthermore, PCR results demonstrated that telmisartan decreased the expression of BCRP expression in liver, intestines and kidney, P-gp expression in the intestines and kidney and OATP1B2 expression in liver tissue. Conclusions Our findings highlight the importance of these drug interactions, which could inform dose adjustments to enhance safety in patients with T2DM and hypertension.